Public Sector Centralization and Productivity Growth: Reviewing the German Experience - Dan Stegarescu; Thiess Büttner; Alexej Behnisch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
The paper examines the role of the vertical structure of the public sector for economic growth in Germany in a long?term perspective. A theoretical model shows that, due to spillover effects of public service provision across lower level governments, federal government activities could have substantially contributed to productivity growth. A review of the German experience starting in the last quarter of the 19th century shows that the overall development is consistent with a stimulating role of the federal government in general and in specific areas like, for instance, transport and communication. However, a further empirical analysis of the period after World War II raises doubts about the efficiency of the vertical structure of the public sector with regard to productivity growth, since the results indicate that a smaller budget share of the state level would have benefited growth.
Keywords: H72; H77; O11; 330; Public sector centralization; public inputs; economic growth; fiscal federalism; Öffentlicher Sektor; Zentralstaat; Öffentliches Gut; Produktivität; Wirtschaftswachstum; Finanzföderalismus; Schätzung; Deutschland